Mortality of welders and other craftsmen at a shipyard in NE England. - Newhouse, M L (1985)
Personnel records of over 1000 welders and electricians but only 235 caulkers and 557 platers employed at a shipyard in NE England between 1940 and 1968 were obtained and the mortality followed up to December 1982. The observed number of deaths (13 from mesothelial tumours, nine among the electricians) were compared with the number to be expected in the Newcastle connurbation. Welders and caulkers were most exposed to welding fumes, electricians to asbestos. The study was limited by the lack of accurate job exposure details, and there was no record of smoking habits, but welders and caulkers showed a higher standardised mortality ratio for all causes, lung cancer, ischaemic heart disease, pneumonia, and accidents than platers and electricians.